Correlation between chord guitar and song year era using apriori algorithm - Rifki Fahrial Zainal; Arif Arizal (Journal of Intelligent Decision Support System (IDSS), 2023)
There are there are more and more varieties of music, especially if you made the music with guitar. There are also many and variety key combinations for the guitar chord. This is usually taken into consideration by beginners who are just learning to play the guitar to make their own music. Music also must made by feeling for the tone itself, and everyone has a different feel. Beginners usually see references from existing songs to made their own music. They usually make it in any key or chord that they want. But they also need inspiration or suggestions for the next key or chord to use from the key or chord they specified. In this study, we propose a way for beginners to find a combination of chords that can be used to make their own first music. From the results of this study, it was found that of the many songs in the database that were released in the 1990s to 2000s, most of them used three combinations of chords Am, Em and G. These three combinations were the combinations that most often appeared in songs. These three keys can become the user's favourites to be used as a basis for making songs or just to find inspiration from songs from the 1990s to 2000s.